HIV and Sexually Transmitted Infection Testing Among High-Risk Youths: Supporting Positive Opportunities With Teens (SPOT) Youth Center - Plax, Katie (Am J Public Health, 2015)
Objectives. We investigated the development of and service utilization at Supporting Positive Opportunities with Teens (SPOT)—a community-based health and social service facility in St. Louis, Missouri, for youths that focuses on increasing HIV and sexually transmitted infection (STI) testing. Methods. We identified the US-based, co-located youth health and social service models that guided the establishment of the SPOT. We analyzed the first 5 years (2008–2013) of service delivery and utilization data. Results. During the study period, the SPOT provided services for 8233 youths in 37 480 visits. The 5 most utilized services included HIV and STI screening, food, transportation, contraception, and case management. A total of 9812 gonorrhea and chlamydia screenings revealed 1379 (14.1%) cases of chlamydia and 437 (4.5%) cases of gonorrhea, and 5703 HIV tests revealed 59 HIV infections (1.0%); 93.0% of patients found to have an STI were treated within a 5-day window. Conclusions. Co-locating health and social services in informal community settings attracts high-risk youths to utilize services and can prove instrumental in reducing STI burden in this population.